IMPLEMENTING DIRECT LEARNING MODEL TO IMPROVE THE BASICTECHNIQUE OF PASSING IN VOLLEYBALL AT GRADE VIISMP NEGERI 18 PEKANBARU - Pesta Simanjuntak (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the result of observations that students had low ability of basic technique of passing in volleyball at grade VII of SMP Negeri 18 Pekanbaru. This study aimed to improve the basic technical skill of passing in volleyball through direct learning model at grade VII of SMP Negeri 18 Pekanbaru. The subjects of this study were 28 students at grade VII of SMP Negeri 18 Pekanbaru. This was classroom action research. The instruments in this research were performance instruments and observation sheets for teacher activities and student activities. Based on the results of the research that has been done, several conclusions were obtained. The initial test of students’ passing ability at grade VII SMP Negeri 18 Pekanbaru obtained an average score of 66.5 (Competent Enough). Then, in Cycle I, the average score of students’ ability increased to 70.9 (competent). In Cycle II, the score increased to 76.8 (Competence) with a percentage of completeness of 100%. Thus, the research hypothesis which was: Direct learning model improved the ability of basic technique of passing in volleyball at grade VII of SMP Negeri 18 Pekanbaru was accepted.